Anaerobic digestion in the fruit waste disposal and valorization - Baumguertner, Matheus Maranho (2020)
It is estimated that around 25% of kiwi fruit production is disposed of as waste. This problem has created an opportunity to evaluated the potential for biogas generation using kiwi waste as a substrate by the anaerobic process, a complex biologic treatment performed in the absence of oxygen, used to stabilize organic matter while producing biogas. Eight distinct assay were performed, were carried out in two batch reactors (R1 and R18). Different substrate/inocu-lum ratios, addition of NaHCO3 and with and without nutrients addition being tested. The most satisfactory results were obtained with: kiwi waste (8.4 g), anaerobic digester slurry (192 mL), sodium bicarbonate (500.4 mg), ammonium chloride (453.0 mg) and potassium phosphate mon-obasic (106.0 mg) added. In this assay, 759.1 mL biogas / g VS was produced and methane quality of 60%.